Hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose high temperature and water resistant sand fixation agent and preparation method and use thereof
By adding hydroxytal and liquid paraffin to the carboxymethyl cellulose, and the free radical aggregation reaction, a high temperature resistant sand -resistant solid -resistant agent is prepared, which solves the easily decomposition and solidification of carboxymethyl cellulose in the existing technology. The problem of low knot intensity and low thermal stability realizes the effective sand fixation of high temperature and rainy coastal sand.
Patent Information
- Application Number
- CN202310757615.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-06-25
AI Technical Summary
In the prior art, carboxymethyl cellulose is very easy to decompose, has low consolidation strength and low thermal stability, making it difficult to adapt to high-temperature and rainy coastal sandy environments.
By subjecting a mixed reaction system containing carboxymethylcellulose salt, hydroxymethylurea, and liquid paraffin to a free radical polymerization reaction under the action of an initiator, hydroxymethylurea-liquid paraffin-carboxymethylcellulose is produced with high temperature resistance. Water-resistant sand-fixing agent.
It improves the mechanical strength and thermal stability of carboxymethyl cellulose, enhances its water erosion resistance, and is suitable for high temperature and rainy coastal sandy environments.
Smart Images

Figure CN116790255B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a sand-fixing agent, in particular to a high-temperature and water-resistant sand-fixing agent of hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose (HDM-Paraffin (L)-CMC) and a preparation method and application thereof, belonging to the technical field of biopolymers and sand-fixing. Background Art
[0002] Desertification seriously threatens global ecological security and the sustainable development of human economy and society, affects 25% of the world's total land area, and threatens the lives of more than 1 billion people in more than 100 countries. It is a major environmental problem and development bottleneck facing the world. Wind and sand activities are typical surface processes in desert areas. Therefore, it is of great significance to take necessary measures to prevent wind and sand.
[0003] Most coastal sandy lands have a subtropical marine climate with high temperatures, abundant precipitation, and distinct dry and wet seasons. For example, Dongshan County in the southern coastal area of Fujian Province has a large annual average precipitation of 945 mm, an annual average temperature of about 21°C, an extreme maximum temperature of 36.6°C, and an extreme minimum temperature of 3.8°C. Therefore, sand fixation agents suitable for this area require good heat and water erosion resistance.
[0004] The long chain structure of carboxymethyl cellulose (CMC) gives it good adhesion and film-forming properties, and it can be used as a sand fixation agent. However, it is very easy to decompose, has low consolidation strength, and its thermal stability needs to be improved. There are abundant amide groups on the molecular chain of acrylamide, which can form abundant hydrogen bond structures and cross-linked networks with various groups. Acrylamide is commonly used in the prior art to enhance the hydrogen bonding between cellulose and its derivatives. However, acrylamide has toxicity and potential risks to human health and the environment. Therefore, it is of great significance to find a new non-toxic substance to replace acrylamide to enhance carboxymethyl cellulose. Summary of the invention
[0005] The invention aims to improve the consolidation strength of the agent by using hydroxymethyl urea and improve the thermal stability and water resistance of the agent by using paraffin wax, and to provide a hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose (HDM-Paraffin (L)-CMC) high temperature and water resistant sand fixation agent suitable for high temperature and rainy coastal sandy land and a preparation method thereof, so as to improve the shortcomings of the prior art that the carboxymethyl fiber is very easy to decompose, has low consolidation strength and low thermal stability.
[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:
[0007] The embodiment of the present invention provides a method for preparing a hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose high temperature and water resistant sand-fixing agent, which comprises: subjecting a mixed reaction system comprising carboxymethyl cellulose salt, hydroxymethyl urea and liquid paraffin to a free radical polymerization reaction under the action of an initiator to obtain the hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose high temperature and water resistant sand-fixing agent.
[0008] In some embodiments, the mass ratio of the carboxymethyl cellulose salt to hydroxymethyl urea is 1:1 to 1:2.
[0009] In some embodiments, the preparation method includes: under the protection of an inert gas, adding an initiator to the mixed reaction system, then heating to 60-90°C, allowing the carboxymethyl cellulose salt and hydroxymethyl urea to undergo a free radical polymerization reaction for 2-5 hours under the action of the initiator to obtain hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose high temperature and water resistant sand fixation agent.
[0010] The embodiment of the present invention also provides a hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose high temperature and water resistant sand fixation agent prepared by the above preparation method.
[0011] Furthermore, an embodiment of the present invention also provides the use of the aforementioned hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose high temperature and water resistant sand fixation agent in the field of sand fixation.
[0012] Compared with the prior art, the beneficial effects of the present invention are:
[0013] The invention utilizes hydroxymethyl urea to enhance the mechanical strength of carboxymethyl cellulose, and utilizes liquid paraffin to enhance the thermal stability and water erosion resistance of carboxymethyl cellulose, so as to prepare a hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose (HDM-Paraffin (L)-CMC) sand-fixing agent with good high temperature resistance and water erosion resistance, which is suitable for sand in high temperature and rainy coastal sandy lands. The agent has excellent high temperature thermal stability and good water erosion resistance, and can be used for preparing sand-fixing materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0015] Figure 1 The figure is a schematic diagram of the preparation of a hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose (HDM-Paraffin (L)-CMC) sand fixation agent in a typical embodiment of the present invention. DETAILED DESCRIPTION
[0016] In view of the shortcomings of carboxymethyl fiber, such as being extremely easy to decompose, having low consolidation strength and low thermal stability, the inventors have proposed the technical solution of the present invention after long-term research and extensive practice, which mainly utilizes hydroxymethyl urea to enhance the mechanical strength of carboxymethyl cellulose, and uses liquid paraffin to enhance the thermal stability and water erosion resistance of carboxymethyl cellulose, so as to prepare a HDM-Paraffin (L) -CMC high temperature resistant and water erosion resistant sand fixation agent suitable for high temperature and rainy coastal sandy land. The technical solution, its implementation process and principles will be further explained as follows. However, it should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described in the following (Examples) can be combined with each other to form a new or preferred technical solution. Due to space limitations, they will not be described one by one here.
[0017] As another aspect of the technical solution of the present invention, a method for preparing a hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose high temperature and water resistant sand-fixing agent is provided, comprising: subjecting a mixed reaction system comprising carboxymethyl cellulose salt, hydroxymethyl urea and liquid paraffin to a free radical polymerization reaction under the action of an initiator to obtain a hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose high temperature and water resistant sand-fixing agent.
[0018] In some embodiments, the preparation method includes: mixing carboxymethyl cellulose salt with water to form a carboxymethyl cellulose salt aqueous solution, and adjusting the pH value of the carboxymethyl cellulose salt aqueous solution to 6-9 (for example, the initial pH value can be 6, 7, 8, 9, etc.), and then adding hydroxymethyl urea and liquid paraffin to form the mixed reaction system.
[0019] In some embodiments, the molar ratio of carboxymethyl cellulose salt, hydroxymethyl urea and liquid paraffin in the mixed reaction system is 1:1:1 to 1:3:3.
[0020] Further, the molar ratio of the carboxymethyl cellulose salt to the hydroxymethyl urea is 1:1 to 1:3, for example, the molar ratio of the two materials can be 1:1, 1:2, 1:3, etc., preferably 1:1 to 1:2. The hydroxymethyl urea (HDM) used in the present invention is a nitrogen-containing organic substance with a molecular formula of C2H6N2O2, containing amide, amino, hydroxyl and carboxyl groups, and is mainly produced by using non-protein nitrogen (NPN) as the main raw material. NPN refers to nitrogen-containing compounds in a non-protein state, including amino acids, peptides, ammonia and its derivatives, urea and its derivatives, amines, phthalamides, hey yin, pyrrolone, nitrates and alkaloids, etc., which are widely present in the body of animals and plants and are non-toxic and naturally degradable materials. Its amino, hydroxyl, and amide groups can replace the hydrogen bonds between acrylamide and cellulose and its derivatives to form a stable cross-linked network and enhance the mechanical properties of cellulose and its derivatives.
[0021] Furthermore, the carboxymethyl cellulose salt includes any one or a combination of two or more of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, potassium carboxymethyl cellulose, calcium carboxymethyl cellulose and ammonium carboxymethyl cellulose, but is not limited thereto.
[0022] In some embodiments, the molar ratio of the liquid paraffin to hydroxymethyl urea is 1:1 to 3:1, preferably 1:1 to 2:1.
[0023] Wax is an edible natural biopolymer with hydrophobic properties. It is a biomaterial suitable for improving the water resistance of coating materials. Wax exists in a solid state at ambient temperature and converts to a liquid state at a higher temperature. Low molecular weight (Mw) wax is in a liquid state at room temperature. Paraffin is an inexpensive water-resistant additive. Liquid paraffin (Paraffin (Liquid), Paraffin (L)) has a melting point of 180-250°C and good heat resistance. Studies have found that paraffin coatings can still maintain their water-repellent properties after being heated at 100°C for 3 hours. The hydroxyl, imino and carbonyl groups in the liquid paraffin used in the present invention can form hydrogen bonds with the hydroxyl groups in carboxymethyl cellulose, and can also form hydrogen bonds with the hydroxyl and amino groups in hydroxymethyl urea to form a highly stable, high-strength, water-resistant viscous solution, which can be used for sand fixation in coastal and tropical sandy areas with high temperature, high humidity and high rainfall.
[0024] In some embodiments, the preparation method may specifically include: under the protection of an inert gas, adding an initiator to the mixed reaction system, then heating to 60-90°C, allowing the carboxymethyl cellulose salt and hydroxymethyl urea to undergo a free radical polymerization reaction for 2-5 hours under the action of the initiator to obtain a hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose (HDM-Paraffin (L)-CMC) high temperature and water resistant sand fixation agent.
[0025] Further, the reaction temperature may be 60° C., 70° C., 80° C., 90° C., etc., but is not limited thereto.
[0026] Furthermore, the reaction time can be 2 h, 3 h, 4 h, 5 h, etc., but is not limited thereto.
[0027] The mechanism of action of the sand-fixing agent prepared by the present invention is that when the HDM-Paraffin (L) -CMC sand-fixing agent is sprayed on the sand tray, the carbonyl group on the hydroxymethylurea chain can react with the inorganic ions in the sand, and at the same time, the calcium carbonate and other substances in the gravel will react with the carboxymethyl cellulose to replace the sodium ions, so that two carboxyl anions and an inorganic cation (such as calcium ions, magnesium ions, etc.) are combined to form a stable network structure, thereby playing a role in fixing sand. Therefore, the HDM-Paraffin (L) -CMC sand-fixing agent with good high temperature and water resistance can be used to prevent and control wind and sand in coastal sandy land with high temperature and heavy rain.
[0028] Further, the initiator may be potassium persulfate (K2S2O8), but is not limited thereto.
[0029] Furthermore, the concentration of the initiator added to the mixed reaction system is 0.05 to 0.25 g / mL, for example, 0.05 g / mL, 0.1 g / mL, 0.15 g / mL, 0.2 g / mL and 0.25 g / mL, but not limited thereto.
[0030] Further, the inert gas may be nitrogen, but is not limited thereto.
[0031] Another aspect of the embodiment of the present invention also provides a high temperature and water resistant sand fixation agent of hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose (HDM-Paraffin (L)-CMC) prepared by the above-mentioned preparation method. The high temperature and water resistant sand fixation agent of hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose has strong high temperature thermal stability, a final degradation temperature of 300°C to 400°C, and a water permeability coefficient of 5.5x10 -4 cm / s~1x10 -3 cm / s, and the compressive strength of the sand-fixing samples is between 3 and 4.5 MPa.
[0032] Correspondingly, another aspect of an embodiment of the present invention further provides the use of any of the aforementioned hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose high temperature and water resistant sand fixation agents in the field of sand fixation, such as the preparation of sand fixation materials or sand fixation devices.
[0033] Through the above technical scheme, the present invention adopts hydroxymethyl urea to enhance the mechanical strength of carboxymethyl cellulose, and uses liquid paraffin to enhance the thermal stability and water erosion resistance of carboxymethyl cellulose, so as to prepare a hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose (HDM-Paraffin (L)-CMC) high temperature and water erosion resistance sand-fixing agent suitable for high temperature and rainy coastal sandy lands. The high temperature thermal stability and water erosion resistance are good, and the sand-fixing agent can be used to prepare sand-fixing materials.
[0034] In order to make the purpose, technical scheme and application of the present invention clearer, the technical scheme of the present invention is further described in detail below in conjunction with several preferred embodiments and drawings. The described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention. The implementation conditions used in the following embodiments can be further adjusted according to actual needs, and the unspecified implementation conditions are usually the conditions in conventional experiments.
[0035] Example 1
[0036] Deionized water is added to sodium carboxymethyl cellulose (CMC) and stirred thoroughly to obtain a CMC aqueous solution. The pH value is adjusted to 8 with an aqueous NaOH solution (analytical grade). Monomer hydroxymethyl urea (HDM, analytical grade) and liquid paraffin (Paraffin (L)) are added to make the molar ratio of each substance: sodium carboxymethyl cellulose: hydroxymethyl urea: liquid paraffin 1:2:2. Then nitrogen is introduced for protection and stirred for 30 minutes. After sufficient dissolution, the initiator potassium persulfate solution (K2S2O8, analytical grade) is slowly added dropwise to make the initiator concentration 0.10g / mL. After the addition is completed, the reaction system is placed in a constant temperature water bath at 80°C. Stir with a stirrer at 500 rpm for 2 hours to allow CMC and HDM to undergo free radical polymerization under the action of the initiator potassium persulfate. The reaction process is as follows: Figure 1 After constant temperature reaction at 80℃ for 2h, the product was precipitated with ethanol (CH3CH2OH, analytical grade) and separated by centrifugation (speed 3500r / min), the product was fully washed with ethanol and purified with acetone (CH3COCH3, analytical grade), and dried at 65℃ to obtain the HDM-Paraffin(L)-CMC sand fixation sample.
[0037] Example 2
[0038] Deionized water is added to sodium carboxymethyl cellulose (CMC) and stirred thoroughly to obtain a CMC aqueous solution. The pH value is adjusted to 8 with an aqueous NaOH solution (analytical grade). Monomer hydroxymethyl urea (HDM, analytical grade) and liquid paraffin (Paraffin (L)) are added to make the molar ratio of each substance: sodium carboxymethyl cellulose: hydroxymethyl urea: liquid paraffin 1:2:2. Then nitrogen is introduced for protection and stirred for 30 minutes. After sufficient dissolution, the initiator potassium persulfate solution (K2S2O8, analytical grade) is slowly added dropwise to make the initiator concentration 0.05g / mL. After the addition is completed, the reaction system is placed in a constant temperature water bath at 80°C. Stir with a stirrer at 500 rpm for 4 hours to allow CMC and HDM to undergo free radical polymerization under the action of the initiator potassium persulfate. The reaction process is as follows: Figure 1After constant temperature reaction at 80℃ for 4h, the product was precipitated with ethanol (CH3CH2OH, analytical grade) and separated by centrifugation (speed 3500r / min), the product was fully washed with ethanol and purified with acetone (CH3COCH3, analytical grade), and dried at 65℃ to obtain the HDM-Paraffin(L)-CMC sand fixation sample.
[0039] Example 3
[0040] Deionized water is added to sodium carboxymethyl cellulose (CMC) and stirred thoroughly to obtain a CMC aqueous solution. The pH value is adjusted to 8 with a NaOH aqueous solution (analytical grade). Monomer hydroxymethyl urea (HDM, analytical grade) and liquid paraffin (Paraffin (L)) are added to make the molar ratio of each substance: sodium carboxymethyl cellulose: hydroxymethyl urea: liquid paraffin is 1:2:2. Then nitrogen protection is introduced and stirred for 30 minutes. After sufficient dissolution, the initiator potassium persulfate solution (K2S2O8, analytical grade) is slowly added dropwise to make the initiator concentration 0.25g / mL. After the addition is completed, the reaction system is placed in a constant temperature water bath at 80°C. Stir with a stirrer at 500 rpm for 5 hours to allow CMC and HDM to undergo free radical polymerization under the action of the initiator potassium persulfate. The reaction process is as follows: Figure 1 After constant temperature reaction at 80℃ for 5h, the product was precipitated with ethanol (CH3CH2OH, analytical grade) and separated by centrifugation (speed 3500r / min), the product was fully washed with ethanol and purified with acetone (CH3COCH3, analytical grade), and dried at 65℃ to obtain the HDM-Paraffin(L)-CMC sand fixation sample.
[0041] The inventors of this case also tested the high temperature thermal stability, mechanical strength, water erosion resistance and other properties of the sand fixation agent obtained in the above examples, and the results are as follows:
[0042] In Example 1, the final degradation temperature of HDM-Paraffin (L)-CMC is 300°C and the water permeability coefficient is 1x10 - 3 cm / s, and the compressive strength of the sand-fixing sample is 3MPa.
[0043] In Example 2, the final degradation temperature of HDM-Paraffin (L)-CMC is 350°C and the water permeability coefficient is 8x10 - 4 cm / s, and the compressive strength of the sand-fixing sample is 4MPa.
[0044] In Example 3, the final degradation temperature of HDM-Paraffin (L)-CMC is 400 °C and the water permeability coefficient is 5.5x10 -4cm / s, and the compressive strength of the sand-fixing sample is 4.5MPa.
[0045] Example 4
[0046] Deionized water is added to lithium carboxymethyl cellulose and stirred thoroughly to obtain a CMC aqueous solution. The pH value is adjusted to 6 with an aqueous NaOH solution (analytical grade). Monomer hydroxymethyl urea (HDM, analytical grade) and liquid paraffin (Paraffin (L)) are added to make the molar ratio of each substance: lithium carboxymethyl cellulose: hydroxymethyl urea: liquid paraffin is 1:1:1. Then nitrogen protection is introduced and stirred for 30 minutes. After sufficient dissolution, the initiator potassium persulfate solution (K2S2O8, analytical grade) is slowly added dropwise to make the initiator concentration 0.15g / mL. After the addition is completed, the reaction system is placed in a constant temperature water bath at 80°C. Stir with a stirrer at 500 rpm for 2 hours to allow CMC and HDM to undergo free radical polymerization under the action of the initiator potassium persulfate. The reaction process is as follows: Figure 1 After constant temperature reaction at 80℃ for 5h, the product was precipitated with ethanol (CH3CH2OH, analytical grade) and separated by centrifugation (speed 3500r / min), the product was fully washed with ethanol and purified with acetone (CH3COCH3, analytical grade), and dried at 65℃ to obtain the HDM-Paraffin(L)-CMC sand fixation sample.
[0047] Example 5
[0048] Deionized water is added to potassium carboxymethyl cellulose and stirred thoroughly to obtain a CMC aqueous solution. The pH value is adjusted to 7 with an aqueous NaOH solution (analytical grade). Monomer hydroxymethyl urea (HDM, analytical grade) and liquid paraffin (Paraffin (L)) are added to make the molar ratio of each substance: potassium carboxymethyl cellulose: hydroxymethyl urea: liquid paraffin is 1:2:1. Then nitrogen protection is introduced and stirred for 30 minutes. After sufficient dissolution, the initiator potassium persulfate solution (K2S2O8, analytical grade) is slowly added dropwise to make the initiator concentration 0.20g / mL. After the addition is completed, the reaction system is placed in a constant temperature water bath at 90°C. Stir with a stirrer at 500 rpm for 5 hours to allow CMC and HDM to undergo free radical polymerization under the action of the initiator potassium persulfate. The reaction process is as follows: Figure 1 After constant temperature reaction at 90℃ for 2h, the product was precipitated with ethanol (CH3CH2OH, analytical grade) and separated by centrifugation (speed 3500r / min), the product was fully washed with ethanol and purified with acetone (CH3COCH3, analytical grade), and dried at 65℃ to obtain the HDM-Paraffin(L)-CMC sand-fixing sample.
[0049] Example 6
[0050] Deionized water is added to ammonium carboxymethyl cellulose and stirred thoroughly to obtain a CMC aqueous solution. The pH value is adjusted to 9 with an aqueous NaOH solution (analytical grade). Monomer hydroxymethyl urea (HDM, analytical grade) and liquid paraffin (Paraffin (L)) are added to make the molar ratio of each substance: ammonium carboxymethyl cellulose: hydroxymethyl urea: liquid paraffin is 1:3:3. Then nitrogen protection is introduced and stirred for 30 minutes. After sufficient dissolution, the initiator potassium persulfate solution (K2S2O8, analytical grade) is slowly added dropwise to make the initiator concentration 0.10g / mL. After the addition is completed, the reaction system is placed in a constant temperature water bath at 60°C. Stir with a stirrer at 500 rpm for 5 hours to allow CMC and HDM to undergo free radical polymerization under the action of the initiator potassium persulfate. The reaction process is as follows: Figure 1 After the reaction was carried out at 60°C for 5 hours, the product was precipitated with ethanol (CH3CH2OH, analytical grade) and separated by centrifugation (speed 3500r / min). The product was fully washed with ethanol and purified with acetone (CH3COCH3, analytical grade). After drying at 65°C, the HDM-Paraffin (L) -CMC sand fixation sample was obtained.
[0051] The inventors of this case also tested the high temperature thermal stability, mechanical strength, water erosion resistance and other properties of the sand fixation agent obtained in the above examples, and the results are as follows:
[0052] In Example 4, the final degradation temperature of HDM-Paraffin (L) -CMC is 320 °C and the water permeability coefficient is 1x10 - 3 cm / s, and the compressive strength of the sand-fixing sample is 3.5MPa.
[0053] In Example 5, the final degradation temperature of HDM-Paraffin (L)-CMC is 380°C, and the water permeability coefficient is 7.8x10 -4 cm / s, and the compressive strength of the sand-fixing sample is 4.3MPa.
[0054] In Example 6, the final degradation temperature of HDM-Paraffin (L) -CMC is 400 °C, and the water permeability coefficient is 6.5x10 -4 cm / s, and the compressive strength of the sand-fixing sample is 4.5MPa.
[0055] Comparative Example 1
[0056] The difference between this comparative example and Example 1 is that no hydroxymethyl urea is added. The final degradation temperature of the obtained sand fixation agent is 250°C, and the water permeability coefficient is 1.5x10 -3 cm / s, and the compressive strength of the sand-fixing sample is 2.54MPa.
[0057] Comparative Example 2
[0058] Compared with Example 1, this comparative example differs in that no liquid paraffin is added. The final degradation temperature of the obtained sand fixation agent is 200°C, and the water permeability coefficient is 2x10 -3 cm / s, and the compressive strength of the sand-fixing sample is 4 MPa.
[0059] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.
[0060] It should be understood that the above examples are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a high temperature and water resistant sand fixation agent of hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose, characterized in that: include: Carboxymethyl cellulose salt is mixed with water to form a carboxymethyl cellulose salt aqueous solution, and the pH value of the carboxymethyl cellulose salt aqueous solution is adjusted to 6-9 with an alkaline substance, and then hydroxymethyl urea and liquid paraffin are added to form a mixed reaction system, wherein the molar ratio of carboxymethyl cellulose salt, hydroxymethyl urea and liquid paraffin in the mixed reaction system is 1:1:1-1:3:3; the structure of the liquid paraffin is as follows: ; Under the protection of inert gas, an initiator is added to the mixed reaction system, and then the temperature is raised to 60-90° C., so that the carboxymethyl cellulose salt and hydroxymethyl urea undergo free radical polymerization reaction for 2-5 hours under the action of the initiator to obtain hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose high temperature and water resistant sand fixation agent, and the concentration of the initiator added to the mixed reaction system is 0.05-0.25 g / mL.
2. The preparation method according to claim 1, characterized in that: The carboxymethyl cellulose salt includes any one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, potassium carboxymethyl cellulose, calcium carboxymethyl cellulose and ammonium carboxymethyl cellulose, or a combination of two or more thereof.
3. The preparation method according to claim 1, characterized in that: The initiator includes potassium persulfate.
4. The preparation method according to claim 1, characterized in that: The inert gas includes nitrogen.
5. A high temperature and water resistant sand-fixing agent of hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose prepared by the preparation method according to any one of claims 1 to 4.
6. The hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose high temperature and water resistant sand fixation agent according to claim 5, characterized in that: The degradation temperature of the hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose high temperature and water resistant sand fixation agent is 300°C to 400°C, and the water permeability coefficient is 5.5 × 10 -4 cm / s ~ 1 × 10 -3 cm / s, and the compressive strength of the sand-fixing samples is between 3 and 4.5 MPa.
7. Use of the high temperature and water resistant sand fixation agent of hydroxymethyl urea-liquid paraffin-carboxymethyl cellulose according to claim 5 or 6 in the field of sand fixation.
Citation Information
Patent Citations
Sand solidification agent and preparation method thereof
CN104550652A
Preparation method for pyrolysis oil urea-formaldehyde resin sand solidification agent
CN105693966A